Numerical investigation on heat transfer and thermoelastic stress in a solar cavity receiver. (5th November 2021) - Fang, Jiabin; Zhang, Canghong; Tu, Nan; Wei, Jinjia; Qaisrani, Mumtaz A.; Wei, Junyao; Zhou, Zhi; Xiao, Bin
Highlights: An optical-thermal-stress computational model was developed. Significant difference in net heat flux was found in boiling and superheated tubes. The origin of thermal stress induced by various temperature gradients was analyzed. Non-linear axial temperature gradient would create an appreciable stress on the tube. Increasing mass flow rate can reduce the thermal stress of the superheated tube. Abstract: Central receiver withstands a highly non-uniform concentrated solar irradiation during its daily operation, which produces temperature gradients in axial, circumferential and radial directions of the absorber tubes, inducing high thermal stress and deformation, even fatigue and creep damage to the tubes. Therefore, an accurate evaluation of thermal stress in receiver tubes is crucial for its safe operation. In the present study, an optical-thermal-stress computational model was adopted to analyze the heat transfer and thermoelastic stress in the absorber tubes of a cavity receiver using water/steam as the heat transfer fluid. The three-dimensional heat flux, wall temperature and thermal stress profiles of the boiling and superheated tubes were obtained. On the basis, the origin of thermal stress were investigated from the perspective of normal stress components and equivalent stress, and special attention was paid to the axial temperature gradient. The results indicate that a significant difference in terms of heat transfer can be observed between the boiling and superheated tubes. In comparison, the peak stress of the superheated tube is 54% higher than that of the boiling tube. Besides, increasing the mass flow rate in the superheated tube can effectively reduce its thermal stress, however this measure is invalid for the boiling tube. Moreover, careful control of boiling to avoid complete evaporation is suggested for the boiling tube, which would create a non-linear axial temperature gradient to the tube, resulting in appreciable stress at the location of sudden variation in wall temperature.